The effects of organisational factors and extra-organisational factors on work stress - Roselina Ahmad Sauf; Leong, Kim Thai; Chua, Bee Seok; Datu Razali Datu Eranza (Penerbit UMS, 2015)
Work stress has been considered as an important issue relating to workers’ day-to- day activities at the work place. In any profession – doctors, teachers, police officers, lawyers and executives – workers are facing enormous pressure from work demands, which results in stress, and burn out. In this millennium, work stress can be considered as a disease of the century. One shall not escape from stress. There are various factors that contribute to work stress. These stem from both organisational and extra-organisational contexts. The aim of this paper is to investigate the impact of both organisational and extra-organisational factors on work stress among married female teachers. The study found that the three organisational factors, namely, management and administration, pupil recalcitrance and time demands were significantly correlated with work stress. As for the extra-organisational factors, only the personal problems variable was found significantly correlated with work stress. A number of studies on teacher stress have been commissioned over the past decade by the major teaching unions.